Effect of botulinum toxin treatment in patients with bruxism and orofacial pain - randomized double-blind clinical trial (Research, Society and Development, 2020)
Introduction: Bruxism is defined as a parafunctional chewing activity characterized by the clenching and / or grinding of teeth that occurs both during sleep and during the surveillance period. Methods: Thirty female patients between 18 and 40 years old who had bruxism and orofacial pain were selected and randomized into two groups: control group (n = 15), where individuals received 0.05 ml of sterile saline solution that was applied to the bundle anterior temporal muscles and 0.2 ml for each masseter muscle, and an experimental group (n = 15), individuals received 20 units of A-botulinum toxin (Botox®) applied to each masseter muscle and 5 units of A-botulinum toxin applied to the anterior bundle of each temporal muscle. Patients were called back for reevaluation every thirty days. At these moments, they underwent an evaluation of the load force and electromyography. Results: At 30, 60, 90 and 120 days, a decrease in electromyographic activity was observed in the A-botulinum toxin group (p